P300 event-related potentials in patients with different subtypes of depressive disorders - Wang, Yun; Li, Canxin; Liu, Xiaohua; Peng, Daihui; Wu, Yan; Fang, Yiru (Frontiers in Psychiatry, 2023)
Objective: To explore the differences in event-related potentials (ERPs) of the subclinical types of major depressive disorders (MDD): melancholic (MEL), atypical (ATY), and anxious (ANX). Results: Finally, 27, 14, and 20 patients with MEL, ATY, and ANX MDD were included in this study, respectively. There were no significant differences in demographic characteristics and HAMD-17, IDS-30SR, and QIDS-16SR total scores among the three groups (all P>0.05). On the C3 lead, the latency for patients with MEL MDD was the longest, and the latency for patients with ATY MDD was the shortest (MEL vs. ATY vs. ANX: 373.89±6.60 vs. 344.79±9.78 vs. 359.33±7.62, P=0.039). On the Pz lead, the latency for patients with MEL MDD was the longest, and the latency for patients with ATY MDD was the shortest (MEL vs. ATY vs. ANX: 376.14±6.51 vs. 347.21±9.42 vs. 362.22±8.63, P=0.047). There were no differences in visual P300 ERPs among the three groups. Conclusion: There are significant differences in auditory C3 and Pz latency among MEL, ATY, and ANX MDD. These differences could help diagnose the subtype of MDD.